Chitin synthase inhibitors as antifungal agents - Chaudhary, Preeti M.; Tupe, Santosh G.; Deshpande, Mukund V. (Mini-Reviews in Medicinal Chemistry, 2013)
Increased risk of fungal diseases in immunocompromised patients, emerging fungal pathogens, limited repertoire of antifungal drugs and resistance development against the drugs demands for development of new and effective antifungal agents. With greater knowledge of fungal metabolism efforts are being made to inhibit specific enzymes involved in different biochemical pathways for the development of antifungal drugs. Chitin synthase is one such promising target as it is absent in plants and mammals. Nikkomycin Z, a chitin synthase inhibitor is under clinical development. Chitin synthesis in fungi, chitin synthase as a target for antifungal agent development, different chitin synthase inhibitors isolated from natural sources, randomly synthesized and modified from nikkomycin and polyoxin are discussed in this review.
Keywords: Antifungal agents; Chitin synthase; Chitin synthase inhibitors; Nikkomycin; Peptidyl nucleoside antibiotics; Polyoxin